Analyzing Student’s Errors in Resolving Questions of Statistics Education in Pokjar Boja, 2018.1 - Eko Andy Purnomo; Martyana Prihaswati; Bambang Dalyono; Sri Handayani (Universitas Muhammadiyah Semarang, 2018)
Lecturers are required to be able to analyze errors in working on the problem along with the causative factors. Through an analysis of errors in doing some exercises, it can be used as a basis in conducting the process of delivering material in the next learning. Through implementing true and mature concepts, students will not face difficulties in applying the material learned. Based on the observations, there are still many students who getdifficulties in doing the exercises of Education Statistics course. Besides, students of Universitas Terbuka in Kaliwungu 2017.2 are lack of learning outcomes in education statistics courses, 2). many students, but do notapply it in learning , 3). Many students do not pass the Education Statistics course. Based on these problems, it is necessary to conduct research related to the analysis of student’s errors and the causal factors in solving the Satistika Education problem. The purpose of this study is to find out the errors and causal factors in solving the questions in the Educational Statistics material. The subject of this research is UT students Semarang 2018.1 in Pokjar in Boja Subdistrict, Kendal Regency. The type of this research is descriptive qualitative research. Based on the analysis of student’s errors in the Education Statistics subject, conclusions are obtained 1). There are 4 student errors, namely: a). conceptual error, b). procedural error, c). Computation / calculation errors, and d).Errors in drawing conclusions; 2). The most mistakes of the students happened on procedural errors; 3). The students’learning difficultiesare caused by the material is large and complex and the time is limited. Keywords: Keywords: Error Analysis, Implementing Concepts, Educational Statistics